PENGARUH ASET PAJAK TANGGUHAN, BEBAN PAJAK TANGGUHAN, DAN PERENCANAAN PAJAK TERHADAP MANAJEMEN LABA (Studi Kasus Pada Perusahaan Infrastruktur Yang Terdaftar di BEI Pada Tahun 2017-2021) - Faizzatul Khasanah; Suprihati Suprihati; Hadi Samanto (ITB AAS INDONESIA, 2023)
This study aims to determine the effect of Deferred Tax Assets, Deferred Tax Expense, and Tax Planning on Earnings Management (Case Study on Infrastructure Sector Manufacturing Companies Listed on the IDX in 2017-2021). The type of research used is quantitative research. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2017-2021. The population used is 14 companies. The sampling technique used was purposive sampling method where the number of observations in this study obtained 70 samples from 14 companies multiplied by 5 periods in this study. Data analysis used was descriptive statistical test method, classic assumption test with hypothesis using Multiple Linear Regression Analysis, F test (simultaneous test), t test (partial test), and R^2 test (coefficient of determination) and assisted by SPSS software version 23 . From the results of the tests that have been carried out, it shows that the variables of Deferred Tax Assets, Deferred Tax Expense, and Tax Planning have a significant effect on Earnings Management. Keywords: Deferred tax assets, Deferred tax expense, and Tax planning.